2019
DOI: 10.3390/ijerph16234770
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Application Practices and Knowledge among Small-Scale Local Rice Growers and Communities in Rwanda: A Cross-Sectional Study

Abstract: Background: Agriculture contributes a third of Rwanda’s GDP and is the main source of income for rural households, with 80% of the total population involved in crop and/or livestock production. The Government of Rwanda established the Muvumba rice project in 2011 amidst a policy shift towards rice as a national staple crop. However, the indiscriminate use of pesticides by local, low-income rice growers has raised concerns about potential human, animal and ecosystem health impacts as pesticide distribution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 24 publications
7
44
1
Order By: Relevance
“…According to Khanal and Singh [37] not considering the wind direction cause uncertainties such as bad odor, unable to spray-on targeted crop, trouble in spraying as well as di culty in inhalation by the person spraying the pesticides. The inadequate knowledge of the pesticide use and methods of the application procedure for this study is in agreement with other studies done in low-income countries [17,36,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…According to Khanal and Singh [37] not considering the wind direction cause uncertainties such as bad odor, unable to spray-on targeted crop, trouble in spraying as well as di culty in inhalation by the person spraying the pesticides. The inadequate knowledge of the pesticide use and methods of the application procedure for this study is in agreement with other studies done in low-income countries [17,36,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…3 Numerous studies in Africa have shown misuse and improper handling of pesticides and poor knowledge of pesticides among farmers in general. 5,6,7,8 This lack of awareness of proper pesticide management practices poses a risk to human health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that several studies have been undertaken to investigate farmers' perception and awareness of pesticide use management and safety measures [17,[23][24][25][26][27][28][29][30], very few studies have assessed the perception of fraudulent pesticides and its determinants among farmers, in particular, in the context of Saudi Arabia. Accordingly, there is a research gap in terms of farmers' perception level of different risk facets of fraudulent pesticides and factors influencing this perception.…”
Section: Introductionmentioning
confidence: 99%